BUKU RAMAH CERNA BERBASIS FOOD SECURITY SEBAGAI UPAYA PENCEGAHAN STUNTING DAN PENINGKATAN LITERASI DINI SISWA SEKOLAH DASAR - Ramadhani, Oktavia Dwi; Fitri, Nazwa Amelia; Fathin, Niswa Maula; Viori, Ravinska Vetra; Rahmalia, Annisa; Aryanto, Sani (Journal of Professional Elementary Education, 2025)
The purpose of this study is to gain a comprehensive understanding of the steps involved in developing an easy-to-digest book based on the concept of Food Security as an effort to prevent stunting and improve early literacy skills among first-grade elementary school students. This research employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects included two validators, three teachers, and ninety first-grade students from SD Negeri Bahagia 06, Bekasi City, who were purposively selected based on educational reports indicating low literacy levels and limited knowledge of nutrition and health. The findings revealed that the easy-to-digest book based on Food Security, developed through stories, engaging illustrations, and interactive reading activities, effectively assisted teachers in teaching early literacy. The book was rated as practical, easy to understand, and relevant to students’ learning needs, receiving an average validation score of 89% categorized as “very good.” Furthermore, the trial implementation showed an increase in students’ reading interest and their understanding of the importance of balanced nutrition and healthy eating habits. Overall, the development of this book successfully integrates literacy, health, and character-building elements as a strategic effort to prevent stunting from an early age.